Internalization of Social Character in Pencak Silat Riksa Raga as Social Studies Learning : Internalisasi Karakter Sosial Dalam Pencak Silat Riksa Raga Sebagai Pembelajaran IPS - Siti Alawiyah, Wini; Mustikarani, Wini; Suherman, Ade (Institut Pendidikan Indonesia, 2022)
Development of thinking skills and character building of students in national education to form a dignified nation. The social character that is formed in the human personality will equip them to be able to live side by side full of love, mutual respect, democracy, mutual cooperation, peace and mutual concern. The purpose of this study was to identify, explore and obtain a factual description of the values ​​of the social character of pencak silat in the Riksa Raga hermitage as a social studies learning resource. The research method used is a quantitative approach with the type of oneshot case study, data collection techniques using questionnaires, interviews and observations. The data analysis technique used validity test, reliability test, normality test, hypothesis test, homogeneity test and descriptive analysis test. The results of this study can be identified (1) there are values ​​that exist in pencak silat, namely religious values, caring values, tolerance values ​​and cooperation values; (2) the values ​​of social character contained in pencak silat such as the value of cooperation, the value of tolerance and the value of caring or solidarity; and (3) having a relatively effective level of efficiency, this is in accordance with the results of the prerequisite test analysis. Therefore, the application of social character values ​​has the effectiveness to be used as a social studies learning resource. So that the values ​​of social character can be used as a source of social studies learning at SMP Fauzaniyyah class VIII with the material of diversity and plurality.